Synergistic Coupling of Co₃O₄ and Ta₂O₅ in Nanostructured Architectures for Simultaneously Enhancing Oxygen Evolution and Urea Oxidation Reaction Kinetics - Casagrande-Denardin, J (Elsevier B.V., 2025)
The growing demand for sustainable energy and clean water solutions has necessitated the design of efficient, stable, and low-cost electrocatalysts. In this study, we present a dual-phase Co₃O₄–Ta₂O₅ nanostructure synthesized via a simple hydrothermal route, followed by thermal annealing. By combining the catalytic activity of Co₃O₄ with the chemical stability of Ta₂O₅, we synthesized a material that performs remarkably well as an electrocatalyst for both the oxygen evolution reaction (OER) and the urea oxidation reaction (UOR). This nanocomposite possesses a unique morphology, containing Co₃O₄ and forming interconnected rod-like structures, with uniformly dispersed Ta₂O₅ particles. Carefully tuning the annealing temperature (400, 600, and 800 °C) allowed us to control crystallinity, phase formation, and surface chemistry. The sample annealed at 800 °C (CoTa-800) exhibited the best performance, offering a low overpotential (400 and 180 mV for the OER and UOR, respectively), small Tafel slopes (105 and 57 mV dec−1), and excellent long-term stability for 25 h. This study highlights that major performance improvements are possible via the meticulous material design, especially via dual-phase engineering and temperature control, of bifunctional electrocatalysis, enabling green hydrogen production and efficient wastewater treatment. © 2025 Elsevier B.V.